Ethnoveterinary medicinal plants application for the treatment of tick-borne diseases in cattle around the Eastern Cape Province of South Africa - Siza Mthi; Jean Rust; Mandla Yawa; Louis Tyasi (AOSIS, 2020)
Background: South Africa is recognised as one of the most biodiverse countries in terms of fauna and flora in the sub-Saharan region. More than 40% of farmers in remote rural areas of the Eastern Cape Province use medicinal plants for the treatment of different livestock ailments. Aim: The aim of the study was to identify and document plant species used for the treatment of tick-borne diseases in the Amathole and O.R. Tambo district municipalities of the Eastern Cape, South Africa. Methods: Semi-structured questionnaire was employed to obtain detailed information of ethnoveterinary medicinal plants used including parts, mode of preparation and mode of administration from 48 respondents between November 2013 and February 2014. The collected plant species were identified scientifically at the Stutterheim Dohne Herbarium, where voucher numbers were obtained and herbarium specimens were deposited. Data collected were subjected to descriptive statistical analysis. Results: A total of nine medicinal plant species belonging to eight families and represented by nine genera were identified. The most dominant inhabitants were trees (55.6%), followed by herbs (33.3%) and shrubs (11.1%). The most frequently used plant families for tick-borne diseases were Xanthorrhoeaceae, Ebenaceae, Proteaceae, Malvaceae, Asteraceae, Vitaceae, Loganiaceae and Iridaceae, and from these plant families, leaves (44.4%) were the most commonly used plant parts. Conclusion: The data display that people in rural areas have preserved some knowledge of ethnoveterinary practices for the treatment of tick-borne diseases. However, further studies on plants used for the treatment of tick-borne diseases can be advanced towards validation and standardisation by evaluating parameters such as efficacy, safety and toxicity, quality (phytochemicals) and dosage standards.